2015
DOI: 10.1007/s00404-015-3813-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary debulking surgery vs. neoadjuvant chemotherapy followed by interval debulking surgery for patients with advanced ovarian cancer

Abstract: NAC followed by IDS provides equal survival compared with PDS. Debulking to small residual tumors with a maximum diameter of less than 1 cm provides a smaller but still significant benefit for patients with PDS but a relatively minor effect with IDS following NAC. To improve the survival of patients with advanced ovarian cancer, the definition of "optimal" in IDS following NAC should be defined as no residual tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 15 publications
(21 reference statements)
5
45
0
Order By: Relevance
“…Subsequently, 11 studies were excluded in which the FIGO stages were III and IV [3, 13-20] or chemotherapies were administered intraperitoneally [21, 22]. Eventually, 12 studies were included in this meta-analysis, comprising 1 RCT [4], 9 cohort studies [1, 11, 23-29], and 2 case-control studies [5, 30]. The flow diagram of study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, 11 studies were excluded in which the FIGO stages were III and IV [3, 13-20] or chemotherapies were administered intraperitoneally [21, 22]. Eventually, 12 studies were included in this meta-analysis, comprising 1 RCT [4], 9 cohort studies [1, 11, 23-29], and 2 case-control studies [5, 30]. The flow diagram of study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 12 studies, 5 studies were arranged with a total of 6 chemotherapeutic cycles [1, 4, 5, 23, 25], including 1,606 patients, with 705 for NAC and 901 for PDS. The characteristics of trials included in this systematic review and meta-analysis are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…114 and 225 patients underwent NACT followed by IDS and PDS, respectively. 26 No difference was observed in progression-free survival (PFS) or overall survival (OS) between NACT group and PDS group (PFS: 11 vs 10 months, P=0.629; OS: 25 vs 25 months, P=0.992). The investigators concluded that NACT followed by IDS provides equal survival compared to PDS.…”
Section: Neoadjuvant Chemotherapy In Epithelial Ovarian Cancermentioning
confidence: 96%